The Turner Prize. - Button, Virginia; Cork, Richard (London : Tate Gallery, 1997)
Since 1984 The Turner Prize has aimed to draw contemporary British art to the attention of a wide audience. With media coverage and visitor numbers increasing each year, its success is not in doubt. But has contraversy flourished at the expense of serious consideration of the artists involved ? Why did the 1992 winner, Grenville Davey, advise future contenders that they would need protective headgear, thick gloves and barrier cream ? In This, the first major book on the award, Virginia Button, curator of the Turner Prize Exhibition since 1993, describes the evolution of the Prize and presents a year by year survey of the artists participating since 1984. Each winner and shortlisted artist is represented by a short illustrated essay. Richard Cork, art critic, introduces the book with a personal view of the importance of the Prize.
Art & Language ; Atkinson, Terry ; Ayres, Gillian ; Borland, Christine ; Bulloch, Angela ; Burgin, Victor ; Caulfield, Patrick ; Chadwick, Helen ; Collins, Hannah ; Cragg, Tony (Anthony) ; Davenport, Ian ; Davey, Grenville ; Deacon, Richard ; Doherty, Willie ; Doig, Peter ; Finlay, Ian Hamilton ; Freud, Lucian ; Gilbert & George ; Gordon, Douglas ; Gormley, Antony ; Hamilton, Richard ; Hatoum, Mona ; Hirst, Damien ; Hodgkin, Howard ; Horsfield, Craigie ; Houshiary, Shirazeh ; Hume, Gary ; Innes, Callum ; Jarman, Derek ; Kalinovska, Milena ; Kapoor, Anish ; Long, Richard ; McGonagle, Declan ; McKenna, Stephen ; Mach, David ; Morley, Malcolm ; Oulton, Thérèse ; Parker, Cornelia ; Penone, Giuseppe ; Patterson, Simon ; Phaophanit, Vong ; Rae, Fiona ; Rego, Paula ; Scully, Sean ; Tremlett, David ; Walker, John ; Wallinger, Mark ; Wearing, Gillian ; Webb, Boyd ; Whiteread, Rachel ; Wilding, Alison ; Wilson, Richard ; Woodrow, Bill
biog. per kunstenaar
The Turner Prize, The Tate Gallery, London, 29.10.1996 - 12.01.1997
Engels
boek
Keywords: Groot-Brittannië